A Comparative Analysis of the Society and State Theories of “Ahlâk-I Alâî” and “Leviathan” Based on the State and Governance-Oriented Paradigms - Yanar, Ömür (European Scientific Journal, ESJ, 2018)
Although Ottoman political thought has been studied in its own structure in many ways, the studies which demostrate its position against different political structures, at least, those in Europe are very limited. Acccordingly, in order to figure out whether this political thought differed in certain respects from one polity to the other, this study has attempted to analyse the society and state theories of “Ahlak-ı Alâî”, which was written in the second half of the 16th century by Kınâlızade Ali Çelebi, who was an Ottoman thinker, and “Leviathan”, which was written by Thomas Hobbes, who was a British philosopher and political theorist in England in the mid- 17th century, in relation to the state and governance-oriented paradigms in a comparative framework. Inspired by the American political theorist Sheldon Wolin, the study has been divided into three sections. The first section presents the socio-economic, political and institutional environment in which the works were written; the second section presents the methods applied in the works. And the last section describes the main message and common ground of the theories. This study has determined that differences and similarities of the methods applied as well as the views argued about the matters such as the legitimacy of the state, the base of the sovereignty, the rights, duties and governance principles of the sovereign based on the temporal and geographical differences in the two works. These findings have significant implications to see the differences and similarities of the Ottoman political thought against political structures in Europe.